MANF antagonizes nucleotide exchange by the endoplasmic reticulum chaperone BiP - Yan, Yahui; Rohland, Lukas (Nature Communications, 2019)
The role of mesencephalic astrocyte-derived neurotrophic factor (MANF) in maintenance of protein folding homeostasis inside the ER has remained unclear. Here the authors determine the structure of the complex between MANF and the ER-localized chaperone BiP and provide evidence that MANF serves as an anti-nucleotide exchange factor for BiP.